Enhanced degradation of carbamazepine in FeOCl based Photo-Fenton reaction. Issue 1 (February 2021) - Sun, Shaobin; Yao, Hong; Fu, Wanyi; Liu, Fang; Wang, Xuewen; Zhang, Wen
Graphical abstract: Highlights: Degradation of CBZ was enhanced by FeOCl based photo-Fenton system. 92 % of CBZ removal was achieved in Photo-Fenton degradation within 30 min. Degradation by-products and pathways of CBZ was elucidated. Effect of common anions on the degradation of CBZ were confirmed. Abstract: Carbamazepine (CBZ) is one of the contaminants of emerging concerns due to its broad distribution in water environments. The present study evaluated various photo-Fenton reactions to achieve enhanced CBZ removal using FeOCl as the photo-Fenton catalyst that exhibited high activity in ·OH generation at a wide range of pH. The effects of UV irradiation, H2 O2 concentration, initial CBZ concentration and catalyst dosage on the CBZ degradation efficiency were evaluated with uncertainty analysis. The H2 O2 concentration of 10 μM, a catalyst dosage of 0.2 g/L, and the initial concentration of CBZ of 100 μM led to the highest CBZ removal rate of 92 % under UV/H2 O2 /FeOCl system within 0.5 h The effects of common anions (i.e., CO3 2−, HCO3, SO4 2−, NO3 - and Cl-) on the CBZ degradation were studied. Three possible degradation pathways and three major degradation by-products were analyzed by LC−ESI−MS, which would provide new insight into the degradation mechanisms of CBZ in photo-Fenton reactions.